2017
DOI: 10.1039/c7qo00608j
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic strategies towards mycolactone A/B, an exotoxin secreted by Mycobacterium ulcerans

Abstract: Pitfalls and dead-ends pave the way to mycolactone A/B. This full account reports synthetic efforts towards this natural product that eventually culminated in a de novo total synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…2014 CAS: 1000770-96-6 Ipomoeassin F Cao et al. 2007 ; Zong et al., 2019 CAS:915392-44-8 Resazurin sodium salt Sigma Aldrich Cat#R7017, CAS:62758-13-8 Mycolactone A/B, mixture of epimers at C12 Saint-Auret et al., 2017a , 2017b N/A Paraformaldehyde Sigma Aldrich Cat#P6148 Deposited Data Canine ribosome:Sec61 complex cryo-EM map in the presence of mycolactone This paper EMDB: 11064 Canine Sec61 channel bound to mycolactone model coordinates This paper PDB: 6Z3T Canine ribosome:Sec61 complex cryo-EM map in the absence of mycolactone This paper EMDB: 11064 Original images and immunoblots, Sanger sequencing, viability assays and LC-MS data This paper https://data.mendeley.com/datasets/cc92fyz9sv/1 Experimental Models: Cell Lines HCT-116 cell line ATCC CCL-247 TRex-293 cell line Thermo Fisher R71007 TRex-293 Sec61α S71F C-terminal Flag This paper N/A TRex-293 Sec61α G80W C-terminal Flag This paper N/A TRex-293 Sec61α S82Y C-terminal Flag This paper N/A Oligonucleotides Sec61A1_frag1F TAGCACTGACGTGTCTCTCG Sigma Aldrich N/A Sec61A1_frag1R TCCCCATACATCCCGGTCAT Sigma Aldrich N/A Sec61A1_frag2F CTTCAACGGAGCCCAAAAGT Sigma Aldrich N/A Sec61A1_frag2R GTGTTGTACT...…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2014 CAS: 1000770-96-6 Ipomoeassin F Cao et al. 2007 ; Zong et al., 2019 CAS:915392-44-8 Resazurin sodium salt Sigma Aldrich Cat#R7017, CAS:62758-13-8 Mycolactone A/B, mixture of epimers at C12 Saint-Auret et al., 2017a , 2017b N/A Paraformaldehyde Sigma Aldrich Cat#P6148 Deposited Data Canine ribosome:Sec61 complex cryo-EM map in the presence of mycolactone This paper EMDB: 11064 Canine Sec61 channel bound to mycolactone model coordinates This paper PDB: 6Z3T Canine ribosome:Sec61 complex cryo-EM map in the absence of mycolactone This paper EMDB: 11064 Original images and immunoblots, Sanger sequencing, viability assays and LC-MS data This paper https://data.mendeley.com/datasets/cc92fyz9sv/1 Experimental Models: Cell Lines HCT-116 cell line ATCC CCL-247 TRex-293 cell line Thermo Fisher R71007 TRex-293 Sec61α S71F C-terminal Flag This paper N/A TRex-293 Sec61α G80W C-terminal Flag This paper N/A TRex-293 Sec61α S82Y C-terminal Flag This paper N/A Oligonucleotides Sec61A1_frag1F TAGCACTGACGTGTCTCTCG Sigma Aldrich N/A Sec61A1_frag1R TCCCCATACATCCCGGTCAT Sigma Aldrich N/A Sec61A1_frag2F CTTCAACGGAGCCCAAAAGT Sigma Aldrich N/A Sec61A1_frag2R GTGTTGTACT...…”
Section: Methodsmentioning
confidence: 99%
“…For selection of stably transfected TRex-293 cells to derive overexpressing mycolactone resistance mutations, we used synthetic mycolactone A/B as a mixture of epimers at C12′, kindly provided by Dr Nicolas Blanchard ( Saint-Auret et al., 2017a , 2017b ) (French National Centre for Scientific Research), which is available in the greater amounts needed for cells under selection. However, tests performed with stable clones used mycolactone A/B ( Song et al., 2002 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 We therefore studied the effects of ipomoeassin F on immune cells and found that its inhibition of membrane receptor expression and cytokine production is comparable to that achieved with mycolactone, Previous studies have illustrated the translational potential of mycolactone against inflammatory disorders 55 , but further exploitation of mycolactone-inspired molecules has been limited by their intrinsic structural complexity that required extensive synthetic efforts. [57][58][59][60][61][62] Given that ipomoeassin variants are easier to generate by synthetic chemistry and equally inhibitory in cellular assays of inflammation, future studies of their pharmacokinetics and therapeutic efficacy against inflammatory diseases and inflammatory pain are an obvious area to pursue in future.…”
Section: A Bmentioning
confidence: 99%
“…Herein, we highlight the key achievements of the different synthetic strategies for the total synthesis of mycolactone A/B and its analogues. An in-depth discussion of the chemistry and biology goes beyond the scope of this article, and can be found in research articles [10][11][12][13][14][15] and reviews. [1,2]…”
Section: Introductionmentioning
confidence: 99%